Injury prevention & performance enhancement: Current trends in athletic shoe design - Hilgers, M. P.; Mayer, B.; Walther, M. (Athletic Therapy Today, 2009)
The purpose of this report is to provide an overview of current concepts in athletic shoe design, with emphasis on running shoes, so that athletic trainers and therapists (ATs) can assist their patients in selection of an appropriate shoe design.